Evolution and Perspectives of Education in Argentina, Coverage and Quality (Cultura Económica, 2018)
The main purpose of this paper is to analyze the education situation of the argentine population in relation to other countries, and its evolution during the last years. It is observed that the "amount of education" continues being very important, though recently there has been a reduction in the enrolment in middle school, as well as a reduction in the enrolment of students in public primary schools. Moreover, the distribution is still very unequal –though less than other inequalities found in Latin America- and its quality, regarding international assessments, is poor in relation with other countries.
Keywords: EDUCATION; ARGENTINE SCHOOL ATTENDANCE; HUMAN CAPITAL; PISA INTERNATIONAL ASSESMENT